Accelerated coronary atherosclerosis and H syndrome. (7th October 2011) - Shankarappa, Ravindranath K; Ananthakrishna, Rajiv; Math, Ravi S; Yalagudri, Sachin Dhareppa; Karur, Satish; Dwarakaprasad, Ramesh; Nanjappa, Manjunath C; Molho-Pessach, Vered
Abstract : A 12-year-old boy with insulin dependent diabetes mellitus, presented with acute myocardial infarction. Intracoronary thrombolysis with urokinase restored TIMI III flow in the culprit vessel. After stabilisation with medical therapy, unusual clinical findings in the form of cutaneous hyperpigmentation and hypertrichosis, affecting the lower extremities, were appreciated. These and other phenotypic features were consistent with H syndrome, a recently described autosomal recessive genodermatosis, and confirmed by mutation analysis. Despite being on optimal medical therapy for coronary artery disease, the patient presented 3 months thereafter, with unstable angina which was successfully managed with percutaneous coronary intervention. An unusual occurrence of coronary artery disease with accelerated atherosclerosis in a child with H syndrome is presented herein. Identification of further patients with this novel disorder will clarify the possible association, suggested here, with increased risk for coronary or other vascular events.